New Endiandric Acid from Beilschmiedia lumutensis and Their Molecular Docking Study as a-amylase and a-glucosidase Inhibitors - Nur Amirah Saad,; Muhammad Solehin Abd Ghani,; Mohammad Tasyriq Che Omar,; Mohd Azlan Nafiah,; Unang Supratman,; Desi Harneti,; Cécile Apel,; Marc Litaudon,; Azeana Zahari,; Khalijah Awang,; Mohamad Nurul Azmi, (Tropical Life Sciences Research, 2026)
A preliminary study showed that an ethyl acetate extract of the bark from Beilschmiedia lumutensis (Lauraceae family) exhibited promising inhibition activities against α-amylase and α-glucosidase by in vitro assays. Subsequently, this extract revealed three new cyclic polyketides endiandric acids, namely lumutensic acid A-C (1–3). Their structures were elucidated by 1D and 2D NMR, FT-IR, HRESIMS spectroscopic data analysis and by comparison with literature data. The molecular docking study showed that lumutensic acid C (3) showed the highest binding affinity and stability with both enzymes, with strong hydrogen bonding and hydrophobic interactions, outperfoming the standard drug acarbose. These findings suggest that compound 3 could be a promising candidate for anti-hyperglycemic therapeutic development, providing further insight into the potential of B. lumutensis as a source of bioactive compounds.